Pengaruh Media Sosial Terhadap Identitas Sosial Remaja Pada Era Digital di SMA Negeri 2 Kota Kupang - Ayu Zeruya Mira Higa (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2025)
The study aims to investigate the impact of social media on teenagers' social identities in the digital era at SMAN 2 Kupang. This study employed quantitative methods, and the data were analyzed using SPSS. The data were then collected through questionnaires, observations, and documentation. Two variables were found as a result of this study: (1) the total percentage of influence of social media on students is 88.61%, and (2) the impact of social media on student identity is 87.39%. As a result, it is reasonable to assume that social media has a significant impact on teenagers' social identities in the digital era at SMAN 2 Kupang. In terms of the validity and reliability analysis test findings on the questionnaire, the indicators have an r-table value of 0.36 and a computed r-value of 0.677, indicating that all are valid. However, the reliability test with a rating of 0.858 suggests that it is exceptionally high or highly reliable. In the simple linear regression test, the significant value (sig) of 0.000 is less than <0.05 probability, therefore Ha is accepted. It is concluded that the use of social media influences the social identity of teens at SMAN 2 Kupang.